Register Analysis of DatingTok Community in TikTok: A Sociolinguistics Study - Anindita, Maharani Laksmi (Universitas PGRI Sumatera Barat, 2025)
Register is a form of language variation that presents a series of new vocabulary and language structures and is used by individuals in certain community groups or certain social situations. One of the communities that produces registers is the social media community. This study aims to understand the form, categorization of meaning, and changes in semantic meaning in the register that appears on TikTok social media, especially in the romance community, or what is known as DatingTok. This study is included in descriptive qualitative research and uses the SBLC method to obtain register data from the DatingTok community from January - March 2025. The results of this study indicate that the register in the community is in the form of words, phrases, and compound words. The meaning of the register is divided into four categories: action-denoting register, relationship-denoting register, individual-denoting register, and activity-denoting register. The register also experiences changes in semantic meaning through broadening, association, and conversion.